The Effect of Postpartum Depressive Symptomatology on the Quality of Early Mother-Newborn Interactions in Morocco. - Ghizlane, Chtabou; Samira, Boulbaroud; Abderrahmane, Boualam; Abdelaati, Soufiani; Hanaa, Elmastini; Bejja, Fadia; Ahmed, Ahami; Kaoutar, Bouktiba; Zahra, Azzaoui Fatima (Bangladesh Journal of Medical Science, 2025)
Background The maternity pathway, which extends throughout pregnancy, undergoes a turning point during the stay in the delivery suite: a place for the installation of early mother-newborn interactions. Objectives: the study aimed is to investigate how depressive symptomatology (DS) affects the quality of early interactions within the dyad. Materials and methods This retrospective study included 102 mother-newborn dyads admitted to the post-natal Unit of the Orangers Maternity Hospital, CHU IBN SINA, Rabat, during the period from April to June 2016. The evaluation utilized the Lille grid, with modifications, to assess the quality of initial bonding, along with the Mother Infant Bonding (MIB) maternal self-questionnaire and the Edinburgh Postnatal Depression Scale (EPDS) for screening postpartum depressive symptomatology (DS). Result The findings indicated that 49% of interactions demonstrated harmony, while 51% exhibited disruptions in the establishment of these interactions, with a prevalence rate of depressive symptomatology (DS) at 38.20%. Disturbances in bonding scores (MIB) were found to be correlated with the mother’s emotional stability (p<0.05) and the quality of the baby’s attachment during breastfeeding (p<0.05). Depressive symptomatology scores (EPDS) were associated with the mother’s understanding of the newborn’s behaviors (p<0.05), gaze appearance (p<0.05), interpretation of crying (p<0.05), and the mother’s availability and affective security (p<0.05). The statistical significance of the effect between maternal depressive symptomatology and issues with early mother-newborn bonding was confirmed (p<0.05), although the magnitude of this effect was relatively low in our sample (Phi V de Cramer=0.248). Conclusion the quality of early interactions depends essentially on the mother’s ability to recognize her place as a mother and her child’s needs. BJMS, Vol. 24 No. 03 July’25 Page : 881-888